Patisiran, an RNAi therapeutic for the treatment of hereditary transthyretin-mediated amyloidosis. (February 2019) - Kristen, Arnt V; Ajroud-Driss, Senda; Conceição, Isabel; Gorevic, Peter; Kyriakides, Theodoros; Obici, Laura
Hereditary transthyretin-mediated amyloidosis is a rapidly progressive, heterogeneous disease caused by the accumulation of misfolded transthyretin protein as amyloid fibrils at multiple sites, and is characterized by peripheral sensorimotor neuropathy, autonomic neuropathy and/or cardiomyopathy. Current treatment options have limited efficacy and often do not prevent disease progression. Patisiran is a novel RNA interference therapeutic that specifically reduces production of both wild-type and mutant transthyretin protein. In Phase II, III and long-term extension studies in patients with hereditary transthyretin-mediated amyloidosis, patisiran has consistently slowed or improved progression of neuropathy. In addition, the Phase III trial demonstrated significant improvements in quality of life measures and indicators of cardiomyopathy. Here, we highlight efficacy and safety data from the patisiran clinical trial programme.